Systematic review and meta‐analysis of post‐transplant diabetes mellitus in liver transplant recipients. Issue 7 (13th June 2021) - Lawendy, Bishoy; Srinathan, Sujitha; Kotha, Sreelakshmi; Gomes, Charlene; Misra, Shruti; Yu, Jeffrey; Orchanian‐Cheff, Ani; Tomlinson, George; Bhat, Mamatha
Abstract: Post‐transplant diabetes mellitus (PTDM) compromises long‐term survival in liver transplant (LT) recipients. The aim of this study was to determine incidence of PTDM after LT and risk factors associated with it. A literature search was conducted, and prospective studies that reported on the incidence of PTDM in LT adult patients on tacrolimus, sirolimus, or cyclosporine were included. We performed random effects meta‐analyses for the incidence of PTDM stratified by immunosuppressant and time period. Of 9817 articles identified, 26 studies were included in the qualitative analysis and 21 studies were eligible for the quantitative analysis representing 79 559 LT recipients in 32 separate treatment arms. The proportion of patients who developed PTDM by two‐three years was 0.15 (95% CI: 0.10–0.24) for cyclosporine, 0.23 (95% CI: 0.14–0.36) for tacrolimus, and 0.27 (95% CI: 0.23–0.30) for sirolimus. Conclusion: Our results showed that sirolimus‐based immunosuppression was associated with a higher incidence of PTDM than tacrolimus or cyclosporine at two‐three years. However, there were only two studies that compared all three drugs which is a limitation of the study and requires more studies with patients on sirolimus. Recipient factors increasing the risk of PTDM are older age, male sex, and high BMI.